The Judges' Academic Background as Determinant of the Quality of Judicial Decisions in Latin American Supreme Courts. (3rd April 2019) - Basabe-Serrano, Santiago
Abstract: This article shows that the academic background of judges will determine the quality of their judicial decisions. Through ordinary least squares models, this research demonstrates that judges with better academic skills are more likely to produce qualitatively better judicial decisions. Contrary to what one would intuitively expect, salaries, workload, type of legal training, and courts specialization do not have a significant influence on the quality of judicial decisions. This research and its results are the first steps to building a comprehensive theory to evaluate the quality of judicial decisions in high courts.